2017
DOI: 10.2337/db17-0382
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microperimetry: A New Tool for Identifying Patients With Type 2 Diabetes at Risk for Developing Alzheimer Disease

Abstract: Type 2 diabetes is associated with a high risk of cognitive impairment and dementia. Therefore, strategies are needed to identify patients who are at risk for dementia. Given that the retina is a brain-derived tissue, it may provide a noninvasive way to examine brain pathology. The aims of this study were to evaluate whether retinal sensitivity ) correlates with the specific parameters of brain imaging related to cognitive impairment and) discriminates patients with diabetes with mild cognitive impairment (MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…In fact, the AUROC of BCEA95 for identifying young morbidly patients with cognitive impairment was 0.807 (CI 95%: 0.592-0.947). We previously reported that retinal sensitivity evaluated by retinal microperimetry was able to identify T2D subjects with cognitive impairment [16]. It should be noted that in this previous study, the T2D patients with Alzheimer's disease and with mild cognitive Impairment were not obese but were insulin resistant.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, the AUROC of BCEA95 for identifying young morbidly patients with cognitive impairment was 0.807 (CI 95%: 0.592-0.947). We previously reported that retinal sensitivity evaluated by retinal microperimetry was able to identify T2D subjects with cognitive impairment [16]. It should be noted that in this previous study, the T2D patients with Alzheimer's disease and with mild cognitive Impairment were not obese but were insulin resistant.…”
Section: Discussionmentioning
confidence: 57%
“…Independent of the fixation and any other eye movement, retinal microperimetry is a strong candidate examination for monitoring AD. It has been indicated that retinal sensitivity evaluated by retinal microperimetry correlated with brain neurodegeneration and could be a novel biomarker for predicting the risk of developing AD among type 2 diabetes patients ( Ciudin et al, 2017 ). Some recent studies have documented more sensitivity of microperimetry in identifying early functional changes of the retina than ERG ( Wu et al, 2014 ).…”
Section: Functional Imaging Methodsmentioning
confidence: 99%
“…Functional assessment of the retina could also be used as an indirect method to explore events in the brain. In a recent prospective study, retinal sensitivity assessed by microperimetry significantly correlated with variables related to brain neurodegeneration and cognitive status [ 84 ]. This pilot study suggested that the assessment of retinal sensitivity by microperimetry could be a useful biomarker for identifying individuals with type 2 diabetes who are at risk of developing Alzheimer’s disease.…”
Section: Retinal Neurodegeneration Is a Biomarker Of Neurodegenerativmentioning
confidence: 99%